Wild Symphony - Brown, Dan; Batori, Susan (New York : Rodale Kids, 2020)
Maestro Mouse embarks on an adventure introducing young readers to animals around the world from elephants to beetles to armadillos. Each animal has a story and life lesson to tell, and Maestro Mouse is ready to share them all. Also, each animal has musical talent, and Maestro Mouse brings all the animals together to create a wild symphony.
new kids book 2023 fall.
Booklist
Kirkus Review
Publishers Weekly
School Library Journal Starred
PS-2.
Keywords: Mice -- Fiction; Conductors (Music) -- Fiction; Stories in rhyme; Animals -- Fiction; Musicians -- Fiction